2002
DOI: 10.1016/s0169-5150(02)00077-4
|View full text |Cite
|
Sign up to set email alerts
|

Under the hood Issues in the specification and interpretation of spatial regression models

Abstract: This paper reviews a number of conceptual issues pertaining to the implementation of an explicit "spatial" perspective in applied econometrics. It provides an overview of the motivation for including spatial effects in regression models, both from a theory-driven as well as from a data-driven perspective. Considerable attention is paid to the inferential framework necessary to carry out estimation and testing and the different assumptions, constraints and implications embedded in the various specifications ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
336
0
21

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(358 citation statements)
references
References 142 publications
1
336
0
21
Order By: Relevance
“…Although the basis for our study is microdata, the analysis is based on aggregated spatial data, which obviously entails disadvantages of ecological fallacies, spurious relations, and the modifiable areal unit problem (Anselin 2002). However, since our interest is in regional differences in partner choice behaviour and its potential explanatory factors on a regional level, we believe that our methodology is justified, although care is needed in the interpretation of results.…”
Section: Methodology Of the Spatial Data Analysismentioning
confidence: 99%
“…Although the basis for our study is microdata, the analysis is based on aggregated spatial data, which obviously entails disadvantages of ecological fallacies, spurious relations, and the modifiable areal unit problem (Anselin 2002). However, since our interest is in regional differences in partner choice behaviour and its potential explanatory factors on a regional level, we believe that our methodology is justified, although care is needed in the interpretation of results.…”
Section: Methodology Of the Spatial Data Analysismentioning
confidence: 99%
“…Identification of these households has been made possible through the advancement in spatial analytical techniques; which has also enables spatial pattern of poverty (concentration of poverty rates and outliers) to be quantified [15], [16], [17]. References [18], [19] showed that poverty rate in nearby locations are likely to be similar to one another, or error for the model in one area or location is correlated with the error terms in its neighboring locations; hence the need to pay attention to the structure of spatial dependence or autocorrelation in our data.…”
Section: Review Of Previous Literaturementioning
confidence: 99%
“…The parameter ρ is the spatial autoregressive or spatial lag parameter. The log-likelihood function for model (1) reads Anselin's (1988):…”
Section: The W-based Autoregressive Modelmentioning
confidence: 99%
“…The approach is based on a spatial weights matrix, usually denoted W, that accounts for spatial dependence or spill-over effects among the spatial units of observation. The selection of a spatial weights matrix is a crucial step in spatial modelling because it a priori imposes a model structure which affects estimates (Bhattacharjee and Jensen-Butler 2006;Anselin 2002;Fingleton 2003) and the substantive interpretation of the research findings (Hepple 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation